2017
DOI: 10.1038/icb.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell activation RhoGTPase‐activating protein plays an important role in TH17‐cell differentiation

Abstract: T-cell activation RhoGTPase-activating protein (TAGAP) is a GTPase-activating protein specific for RhoA that is exclusively expressed in activated T cells. Genome-wide association studies and metagenome SNPs analyses have indicated that TAGAP is associated with the pathogenesis of multiple autoimmune diseases, including psoriasis, rheumatoid arthritis, Crohn's disease, celiac disease and multiple sclerosis. However, the precise function of TAGAP remains unclear. Because T17 cells contribute to TAGAP-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…Thus, genes related with immune response, either by promoting leukocyte growth or favoring migration or activation are strong candidate genes. For instance, in Atlantic salmon we found T-cell activation Rho GTPase-activating protein (TAGAP) which participates in the activation and recruitment of T cells by cytokines 33 , and tenascin R (TNR) which is an extracellular matrix protein, present in bone marrow, thymus, spleen and lymph nodes 34 . The latter has been described as having an adhesin function favoring the mobility of lymphocytes and lymphoblasts 34,35 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, genes related with immune response, either by promoting leukocyte growth or favoring migration or activation are strong candidate genes. For instance, in Atlantic salmon we found T-cell activation Rho GTPase-activating protein (TAGAP) which participates in the activation and recruitment of T cells by cytokines 33 , and tenascin R (TNR) which is an extracellular matrix protein, present in bone marrow, thymus, spleen and lymph nodes 34 . The latter has been described as having an adhesin function favoring the mobility of lymphocytes and lymphoblasts 34,35 .…”
Section: Resultsmentioning
confidence: 99%
“…TAGAP inhibits the binding of Zap70 to the adapter RhoH, thereby reducing the strength of the TCR signal . Reduced Th17 differentiation was observed in TAGAP –/– T cells and this was associated with a milder experimental autoimmune encephalomyelitis (EAE) phenotype . These studies did not address differentiation of other Th cell subsets, or examine IL‐2 production, so it is not clear how this study fits into the body of work suggesting that high TCR signals are required for Th17 differentiation.…”
Section: Tcr Signalling Pathways and Th Cell Differentiationmentioning
confidence: 98%
“…Several other signalling molecules have been implicated in Th cell subset differentiation, including Nck, MALT1, Pak2, Notch and other early components of the TCR signalling pathway . Another study identified a role for T‐cell activation RhoGTPase‐activating protein (TAGAP) in Th17 differentiation . TAGAP inhibits the binding of Zap70 to the adapter RhoH, thereby reducing the strength of the TCR signal .…”
Section: Tcr Signalling Pathways and Th Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell activation Rho GTPase-activating protein (TAGAP) is a GTPase-activating protein, and many single nucleotide polymorphisms (SNPs) near or within the TAGAP gene have been found to be associated with susceptibility to many autoimmune diseases and infectious diseases, including MS, Crohn's disease, psoriasis, RA, celiac disease, and candidemia [17][18][19][20][21] . TAGAP protein is a GAP domain containing protein, and previous study found that TAGAP has a role in T-cell differentiation 22,23 . Here, we report that TAGAP is required for Dectin-1, Dectin-2/3 and mincle ligands-induced signaling pathway activation and proinflammatory induction in macrophages.…”
mentioning
confidence: 99%